2021
DOI: 10.1002/rmv.2261
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orally administered lactoferrin in the prevention and management of viral infections: A systematic review

Abstract: It has been demonstrated that lactoferrin (LF) plays a role in host defence, but evidence on its potential antiviral property from clinical studies is fragmented. Our systematic review aimed at identifying the effects of orally administered LF against virus infections. The systematic search was conducted on PubMed, Scopus, Web of Science, BioRxiv.org and ClinicalTrials.gov from database inception to 7th January 2021. Eligible articles investigated any virus family and provided data on the effects of orally adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…It has been reported that vitamin D modulates both the adaptive immune and innate immune systems from in vitro studies and animal studies. First, vitamin D could work as a direct and indirect regulator of T cells [7]. Vitamin D regulates T cells directly by inhibiting T cell proliferation, Interleukin-2 (IL-2) and Interferon-γ (INF-γ) transcription, and IL-17 secretion by helper T 17 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that vitamin D modulates both the adaptive immune and innate immune systems from in vitro studies and animal studies. First, vitamin D could work as a direct and indirect regulator of T cells [7]. Vitamin D regulates T cells directly by inhibiting T cell proliferation, Interleukin-2 (IL-2) and Interferon-γ (INF-γ) transcription, and IL-17 secretion by helper T 17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against influenza, pneumococcus, and tuberculosis is also being used for the primary prevention of ARIs. Additionally, although oral zinc, vitamin C supplements, vitamin D supplements, ginseng, and probiotics have been suggested to have a preventive effect on the development of ARIs in some studies, this remains inconclusive [5,6], whereas a meta-analysis of six randomized controlled trials (RCTs) reported that lactoferrin supplements, as one of the key immunomodulatory substances, had efficacy in reducing the risk of RTIs [7].…”
Section: Introductionmentioning
confidence: 99%
“…They recommend increasing the amount of elemental iron to 60-120 mg/day in pregnancies associated with anemia [34]. Despite iron pills being the most common type of supplementation, recent studies debate the use of lactoferrin in treating anemia in pregnant women [35], with potential benefits in the context of preventing and managing COVID-19 [36]. The Network for the Advancement of Patient Blood Management, Hemostasis, and Thrombosis consensus statement also recommends daily oral iron supplementation with 30-60 mg/day in areas where there is a high prevalence of anemia during pregnancy and screening for iron deficiency in all pregnancies at risk of iron deficiency [37].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They suggested that this treatment option might be considered in asymptomatic or paucisymptomatic patients to avoid the worsening of SARS-CoV2. The few studies that enrolled patients showed a shortening of the conversion of the rRT-PCR SARS-CoV2 RNA and lower IL-6 and D-Dimer levels, and a decrease of the length of symptoms has been highlighted [ 40 ]. It is important to mention that neither RCTs nor meta-analysis are currently available and further research is needed in order to better define the role of lf in the management of the current pandemic.…”
Section: Resultsmentioning
confidence: 99%